2012
DOI: 10.1007/s10803-012-1736-0
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychological Profile in High Functioning Autism Spectrum Disorders

Abstract: A comprehensive investigation of the neuropsychological strengths and weaknesses of children with autism may help to better describe their cognitive abilities and to design appropriate interventions. To this end we compared the NEPSY-II profiles of 22 children with high-functioning autism spectrum disorders (HFASD) with those of 44 healthy control (HC) children 2:1 matched by gender, age, race and education. Results showed that only Visuospatial Processing was relatively spared in HFASD, while deficits were ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
59
2
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 97 publications
(76 citation statements)
references
References 86 publications
10
59
2
2
Order By: Relevance
“…Our finding of poorer performance in children with ASD compared to TD children on Language domain is consistent with previous studies using NEPSY (Hooper et al, 2006;Korkman et al, 2007;Narzisi et al, 2013). Also, our results concur with other studies on language deficits in children with ASD and expanded the findings as affecting also children with ASD + ADHD.…”
Section: Language Domainsupporting
confidence: 93%
See 3 more Smart Citations
“…Our finding of poorer performance in children with ASD compared to TD children on Language domain is consistent with previous studies using NEPSY (Hooper et al, 2006;Korkman et al, 2007;Narzisi et al, 2013). Also, our results concur with other studies on language deficits in children with ASD and expanded the findings as affecting also children with ASD + ADHD.…”
Section: Language Domainsupporting
confidence: 93%
“…In line with the earlier ASD studies (Hooper, Poon, Marcus, & Fine, 2006;Korkman, Kirk, & Kemp, 2007;Narzisi et al, 2013), that used NEPSY, our sample of children with ASD and ASD + ADHD faired worse than TD children in their ability to judge line orientation. However, there is another study that employed another study (Narzisi et al, 2013).…”
Section: Visuospatial Processing Domainsupporting
confidence: 84%
See 2 more Smart Citations
“…1 The disorder has a heterogenous phenotype, in relation to both symptoms and severity. 2 Several studies conducted from the point of view of the healthcare professional/physician indicated that individuals with ASD are resistant to change and have a narrow range of interests that may affect even the food they eat.…”
Section: Introductionmentioning
confidence: 99%